A design odyssey in the built environment: functionality, aesthetics and heritage - Othman, Rashidi (Nova Science Publishers, Inc., 2025)
A Design Odyssey in the Built Environment: Functionality, Aesthetics and Heritage, presents a multidisciplinary collection of research that explores the dynamic relationship between design practices and the built environment. The chapters’ address core themes such as human perception in spatial and chromatic environments, traditional crafts and architecture preservation, and integrating functionality and aesthetics in contemporary design. The book emphasises the importance of culturally responsive and environmentally conscious approaches to space-making, material use, and visual expression through these discussions. The contributions also reflect ongoing efforts to reconcile tradition with innovation, particularly in sustainable development and social integration. Topics range from conservation strategies for heritage sites and natural dyes to the design of workspaces, science centres, and community spaces informed by local identity. This collection is a scholarly platform for advancing dialogue on how design can support heritage continuity, community well-being, and ecological resilience within the broader discourse of architecture, landscape architecture, interior design, and applied arts.